Causal relationship model of factors influencing sustainability preferences in community-based tourism in Thailand - Nilwan, Dejawit; Chartrungruang, Bung-on; Mukdasanit, Supachai; Jaikaew, Ardchawin; Trongwattanawuth, Sirirat (Kasetsart Journal of Social Sciences, 2026)
The purpose of this research was to study the consistency between the causal relationship model of factors influencing Sustainability Preferences (SUS) in Community-Based Tourism (CBT) in Thailand and empirical data, while also analyzing the direct and indirect effects of variables within the model. The sample consisted of 200 domestic tourists and 200 foreign tourists, totaling 400 individuals visiting CBT destinations. Descriptive statistics, including frequency, mean, percentage, and standard deviation, were employed for validation and analysis, alongside confirmatory factor analysis and path analysis. The findings indicated a strong fit between the causal relationship model and empirical data (x2= 98.514, df = 81, p = .09, CFI = 0.996, AGFI = 0.938, GFI = 0.976, RMR = 0.010, and RMSEA = 0.023), so it can be seen that all-important statistical indices meet the specified criteria. The variables of the model could describe 96 percent with SUS directly affected by Attractiveness (AT) and Tourist Experiences (TE) with the effect sizes 0.08 and 0.88, respectively. Moreover, SUS was indirectly affected by AT and TE through Community Involvement (CI) with the effect size 0.370 and 0.247, respectively.